Direct and Indirect Measurements for a Better Understanding of the Primordial Nucleosynthesis - Spartá, Roberta; Pizzone, Rosario Gianluca; Bertulani, Carlos A.; Hou, Suqing; Lamia, Livio; Tumino, Aurora (Frontiers in Astronomy and Space Sciences, 2020)
The Big Bang Nucleosynthesis (BBN) model is a great success of nuclear astrophysics, because of the outstanding agreement between observational and predicted light elements abundances, except for the so-called "lithium problem". In this context, experimental efforts to measure the relevant reactions have brought to an increased level of accuracy in measuring primordial abundances and the introduction of indirect methods has allowed to overcome the natural limitations of direct measurements in the energy range of interest for BBN. Here we review the results obtained from the application of the Trojan Horse Method to some of the most influential reactions of the standard network, such as $^2$H(d,p)$^3$H, $^2$H(d,n)$^3$He, $^3$He(d,p)$^4$He, $^7$Li(p,$α$)$^4$He and $^7$Be(n,$α$)$^4$He. The relevant cross sections have been thus used as new inputs of a classical BBN code resulting in important constraints that advice on a possible solution of the lithium problem outside of nuclear physics.